Role of renewable energy and storage in low-carbon power systems - Wang, Weiru; Cheng, Xueting; Li, Jing; Zheng, Huiping; Li, Mengzan (Frontiers in Energy Research, 2024)
To promote the achievement of low-carbon goals in the power industry, rational and effective power system planning is essential. The participation of demand response in power system planning is an important means to reduce carbon emissions. To this end, a dual-layer low-carbon planning model for power systems considering carbon emission flow and demand response was designed. The upper layer investment planning model minimizes investment and operational costs, using an annual 8760-h operation simulation model and unit clustering linearization of the coal-fired units, coordinating the optimized investment and construction capacity of traditional units, new energy, and storage. The lower layer model forms a demand response model based on carbon emission flow theory and a load-side stepped carbon price mechanism, using the unit output and line flow data calculated by the upper layer model. This model reasonably adjusts the load distribution to reduce both the amount and cost of carbon emissions. Finally, the proposed model was analyzed and verified on the improved IEEERTS-24 node system.